Tinjauan Metode Screening Saham Syariah Pada Bursa Efek Indonesia - Rahmawati Muin; Murtiadi Awaluddin; Islahuddin Islah (Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims to determine how the screening method of sharia stocks in Indonesia, how the results of screening of sharia stocks in PT Adaro Energy Tbk, and the review of the methods of sharia screening stocks in Indonesia Stock Exchange (IDX). The results showed that the stocks issuer is conform the sharia stock screening standards, beside that, maslahah mursalah could be used as a methodology to determine sharia stock screening standards, then the Financial Services Authority (OJK) and DSN-MUI, as well as the Indonesia Stock Exchange (IDX), have to revise the screening standards in progressively and periodically to avoid public misperception of sharia stock screening.